MEMAHAMI FENOMENA CYBERBULLYING YANG TERJADI TERHADAP TRANSGENDER - Anastasya Yuca Venina; Hapsari Dwiningtyas Sulistyani; Lintang Ratri Rahmiaji (Interaksi Online, 2022)
Cyberbullying is an act of uploading or sending messages or images that are abusive and harmful through the digital media or internet that can happen to anyone, including transgender. This study aims to understand the communication process and mindset that can be the reason for someone to do cyberbullying. Qualitative research methods and Interpretative Phenomenological Analysis (IPA) approach are used in this study. The theories used as a reference are new media theory, social prejudice theory, and social norm theory. Based on this study, the three informants confirmed the existence of cyberbullying against transgender in social media Instagram. During the 6 (six) months of observation period, there are 3 (three) forms of cyberbullying found, namely flaming, harassment, and denigration. This study found that besides prejudice and social norm embraced by each informant, personal factors such as problems with self-ability, getting influenced by their surroundings, and also envines are the important factors that trigger cyberbullying. In addition, the cyberbullies misinterpret the freedom of expression by using a fake account while they are doing cyberbullying because they feel more comfortable to express their opinion because of the anonymit. The communication process carried out is that the cyberbullies choose whether they want to communicate it to someone else or not and two of the three informants who communicated it to someone else feel that they get a support and also validation so that they consider cyberbullying as a normal thing to do.